Existence of multiple solutions for a p-Kirchhoff problem with the non-linear boundary condition. Issue 16 (10th December 2018) - Li, Qin; Yang, Zuodong
ABSTRACT: In this paper, using the Nehari manifold and fibering maps, we study the existence of at least two positive solutions for the following p -Kirchhoff equation where is a bounded domain, with a, b, , is the p -Laplacian operator, is a parameter.